Screening of high-Z grains and related phenomena in colloidal plasmas - Bystrenko, O.; Bystrenko, T.; Zagorodny, A. (Condensed Matter Physics, 2003)
Recent important results are briefly presented concerning the screening
of high-Z impurities in colloidal plasmas. The review focuses on the phenomenon
of nonlinear screening and its effects on the structure of colloidal
plasmas, the role of trapped ions in grain screening, and the effects of
strong collisions in the plasma background. It is shown that the above effects
may strongly modify the properties of the grain screening giving rise
to considerable deviations from the conventional Debye-Huc¨ kel theory as
dependent on the physical processes in the plasma background. Подано стислий виклад важливих останніх результатів по екрануванню сильнозаряджених домішок в колоїдній плазмі. В центрі уваги огляду – нелінійне екранування та його вплив на структуру колоїдної плазми, роль зв’язаних іонів в екрануванні макрочастинок та
ефекти сильних зіткнень в плазмовому середовищі. Показано, що
ці явища можуть сильно впливати на властивості екранування макрочастинок, призводячи до значних відхилень від традиційної теорії
Дебая-Гюкеля, в залежності від фізичних процесів у плазмовому середовищі.